2018
DOI: 10.1080/20008198.2018.1486121
|View full text |Cite
|
Sign up to set email alerts
|

Exploring resilience models in a sample of combat-exposed military service members and veterans: a comparison and commentary

Abstract: Background: The term resilience is applied in numerous ways in the mental health field, leading to different perspectives of what constitutes a resilient response and disparate findings regarding its prevalence following trauma. Objective: illustrate the impact of various definitions on our understanding and prevalence of resilience, we compared various resilience definitions (absence of PTSD, absence of current mental health diagnosis, absence of generalized psychological distress, and an alternative trauma l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 51 publications
2
26
1
Order By: Relevance
“…In line with previous literature (Nishimi, Choi, Cerutti, et al, 2020;Sheerin et al, 2018), we found that self-assessed coping ability and outcome-based psychiatric resilience were only moderately correlated with each other, indicating these may reflect different patterns of adaptive functioning following adversity. Collectively, our research adds to the growing literature on the nature of resilience as a construct.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with previous literature (Nishimi, Choi, Cerutti, et al, 2020;Sheerin et al, 2018), we found that self-assessed coping ability and outcome-based psychiatric resilience were only moderately correlated with each other, indicating these may reflect different patterns of adaptive functioning following adversity. Collectively, our research adds to the growing literature on the nature of resilience as a construct.…”
Section: Discussionsupporting
confidence: 91%
“…Resilience is generally conceptualized as maintained mental health or positive adaptation despite trauma exposure (Choi, Stein, Dunn, Koenen, & Smoller, 2019;Kalisch et al, 2017;Luthar, Cicchetti, & Becker, 2000). The two most widely used approaches to operationalize the concept define resilience as perceived coping ability reflecting a stable tendency to cope effectively with stress and adversity (Campbell-Sills & Stein, 2007;Connor & Davidson, 2003), and as psychiatric resilience reflecting an empirically derived outcome, such as the absence of PTSD or other psychiatric disorders among individuals exposed to adversity (Nishimi, Choi, Cerutti, et al, 2020;Sheerin, Stratton, Amstadter, The VA Mid-Atlantic Mental Illness Research, Education, Clinical Center (MIRECC) Workgroup., & McDonald, 2018). The different resilience definitions are not mutually exclusive, but rather complementary and may capture different underlying dimensions of resilience (Choi et al, 2019;Fisher & Law, 2021;Sheerin et al, 2018) .…”
Section: Introductionmentioning
confidence: 99%
“…Biopsychosocial mechanisms and processes involved in the long-term adverse impact of childhood trauma over decades into mid-life and old age (Glück, Knefel, Tran, & Lueger-Schuster, 2016) and across generations (Kuffer, Thoma, & Maercker, 2016) have been preliminarily conceptualized but remain understudied. We do not know how, for whom, and under what circumstances trajectories of post-traumatic resilience emerge across the lifespan, although we are beginning to understand that resilience is a complex and multifaceted phenomenon that warrants much further study (Iacoviello & Charney, 2014;Nugent, Sumner, & Amstadter, 2014;Sheerin, Stratton, Amstadter, & McDonald, 2018;Southwick, Bonanno, Masten, Panter-Brick, & Yehuda, 2014), particularly in order to inform enhancements of trauma-focused therapies based on promoting resilience (Schnyder, 2014).…”
Section: Trauma Exposure and Impact Across The Lifespanmentioning
confidence: 99%
“…This discrepancy-based psychiatric resilience measure, referred to hereafter as DBPR, has been examined in behavioural genetic (Amstadter, Moscati, Maes, Meyers, & Kendler, 2016), epidemiologic (Sheerin et al, 2018a), and combat-specific (Sheerin, Stratton, Amstadter, MIRECC workgroup, & McDonald, 2018b) samples, and has been previously demonstrated to protect against development of later internalizing disorders, even in the context of new-onset stressors (Sheerin et al, 2018a). DBPR has a modest correlation with the CD-RISC (Sheerin et al, 2018b), suggesting, as one would expect, these two measurements of resilience are meaningfully related yet are not tapping into a unitary construct. A remaining question is whether this index of resilience is useful when expanded to the examination of its association with other outcomes, above and beyond other known predictors.…”
Section: 目的:尽管战斗暴露与一系列精神病有关,但许多退伍军人并未发展出精神病理。韧性mentioning
confidence: 99%